1997
DOI: 10.1021/om960994v
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity in Group 14 Metalloles:  Structural, Energetic, and Magnetic Criteria

Abstract: Various structural (C−C bond length equalization, D), energetic (isodesmic stabilization energies, ISE), and magnetic (diamagnetic susceptibility exaltations, Λ and nucleus-independent chemical shifts, NICS) criteria are employed (using B3LYP, CSGT, and GIAO ab initio methods) to assess the aromaticity and antiaromaticity of a variety of group 14 (E = C, Si, Ge, Sn, Pb) metalloles:  C4H4EH2 (C 2 v ), C4H4EH- (C s and C 2 v ; C, D 5h ), C4H4EH+ (singlet, C 2 v ), C4H4EHLi (C s ; C, C 5v ), and C4H4ELi2 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(57 citation statements)
references
References 46 publications
6
46
2
3
Order By: Relevance
“…These chemical shifts of 29 Si and 13 C resonances are consistent with delocalization of the negative charge into the silole ring, which is supported by the calculated negative NICS value of dilithiumsilole dianion [9,10]. In addition the signals of the ethyl groups in the 1 H- and 13 C-NMR spectra of 3 shift downfield due to the anisotropic effect of the ring current from the delocalization {Δδ( 13 C of CH 2 CH 3 ) = 1.42–7.83 ppm and Δδ( 1 H of CH 2 ) = 0.16–0.19 ppm)} (Table 3).…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…These chemical shifts of 29 Si and 13 C resonances are consistent with delocalization of the negative charge into the silole ring, which is supported by the calculated negative NICS value of dilithiumsilole dianion [9,10]. In addition the signals of the ethyl groups in the 1 H- and 13 C-NMR spectra of 3 shift downfield due to the anisotropic effect of the ring current from the delocalization {Δδ( 13 C of CH 2 CH 3 ) = 1.42–7.83 ppm and Δδ( 1 H of CH 2 ) = 0.16–0.19 ppm)} (Table 3).…”
Section: Resultssupporting
confidence: 70%
“…Since the first silole dianion, 2,3,4,5-tetraphenyl-1-silacyclopentadienide dianion, was prepared in 1990 by Joo and Hong [1], the aromaticity of the silole dianion [2] and germole dianion [3] was suggested by NMR study and it was confirmed by X-ray crystallography of the structures [4,5,6,7,8] and by theoretical study [9,10]. The chemistry of group 14 metallole dianions has been developed enormously [11,12], and recently the stannole dianion [SnC 4 Ph 4 ] 2− was also reported [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic criteria including NICS of Silole dianions and metaloles containing Si, Ge, Sn, and Pb have been reported. [9,10] Pioneering theoretical calculations of metal NMR [11,12] were helpful for the present analyses. The relativistic correction, especially the spinorbit effect, is essentially required in heavy-element NMR chemical shifts.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence quantum yields of the germole analogs of DMTPS and HPS are 0.28 and 0.63%, respectively, compared with 0.24 and 0.42% for the siloles. Compared with the siloles, relatively few germoles or reports of their AIE behavior have been described in the literature [4,8,104,[107][108][109][110].…”
Section: Germolesmentioning
confidence: 99%